1979
DOI: 10.1104/pp.63.4.643
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Action of Benzyladenine and Other Chemicals on Flowering of Pharbitis nil Chois

Abstract: Benzyladenine (BA) brushed on the cotyledons of 4-day-old seedlings of Pharbitis nil Chois. markedly stimulates flowering. Greatest response is obtained for concentrations between 44 and 440 micromolar. The action of BA is on processes in the cotyledon as shown by the response to its site of application, to the dosage applied and to the requirement for its application prior to the dark period. There was little or no effect of BA Two other chemicals which were previously considered as specific inhibitors of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The vegetative sinks in the present experiments were young leaves approaching their peak strength (20). Similar compensatory changes in the export pattern from cotyledons of Pharbitis nil in response to differential treatment of the cotyledons have been shown recently by Ogawa and King (17).…”
Section: Resultssupporting
confidence: 91%
“…The vegetative sinks in the present experiments were young leaves approaching their peak strength (20). Similar compensatory changes in the export pattern from cotyledons of Pharbitis nil in response to differential treatment of the cotyledons have been shown recently by Ogawa and King (17).…”
Section: Resultssupporting
confidence: 91%
“…In Pharbitis nil, assimilate allocation to induced apices was studied with BA treatments (Ogawa and King 1979). BA was applied to indueed and non-induced cotyledons of Pharbitis nil, and the authors showed that BA promotion of flowering was due to the interference of BA with assimilate translocation from the cotyledons to the apices.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of P. nil cotyledons to a dark period of 16 h results in flowering (Imamura, 1961). If one cotyledon is kept in continuous light (CL), however, the floral response to a single inductive dark period can be reduced (Imamura, 1961;Ogawa and King, 1979). Using apex cultures from P. nil as an assay system, the phloem exudates (PE) extracted from P. nil cotyledons grown under SD conditions gave flower-inducing activity (Ishioka et al, 1990(Ishioka et al, , 1991, whereas the exudates from cotyledons grown under CL conditions showed flower-inhibiting The photoperiodic conditions and treatments were described as in ''Materials and methods''.…”
Section: Discussionmentioning
confidence: 99%